8
$\begingroup$

Prove that $$\int_{0}^{\frac{\pi}4} \ln(\sin{x}+\cos{x}+\sqrt{\sin{2x}})dx =\frac{\pi}{4} \ln2$$

I tried to use King's rule and to scale by $2$ and then to add the integrals, to get product of terms and use the result $$\int_{0}^{\frac{\pi}2} \ln(\sin{x})dx=\int_{0}^{\frac{\pi}2} \ln(\cos{x})dx=-\frac{\pi}2\ln2$$ but it didnt work. Any help?

$\endgroup$
  • $\begingroup$ @Zacky i was experimenting with mathematica ! $\endgroup$ – Grentouce Jul 25 '19 at 12:02
  • $\begingroup$ Standard techniques will work. $\endgroup$ – Axion004 Jul 25 '19 at 12:02
  • $\begingroup$ @Axion004 like what?that sqaure root is annoying...help plz $\endgroup$ – Grentouce Jul 25 '19 at 12:03
15
$\begingroup$

$$I=\int_{0}^{\frac{\pi}4} \ln(\sin{x}+\cos{x}+\sqrt{\sin(2x)})dx =\frac12 \int_0^\frac{\pi}{2} x'\ln(\sin x+\cos x+\sqrt{\sin (2x)})dx$$ $$\overset{IBP}=\frac12 \int_0^\frac{\pi}{2}x\,\frac{\sin x-\cos x}{\sqrt{\sin(2x)}}dx\overset{x=\arctan t}=\frac{1}{2\sqrt 2}\int_0^\infty \frac{\arctan t}{1+t^2}\frac{t-1}{\sqrt t}dt$$


$$I(a)=\int_0^\infty \frac{\arctan(at)}{1+t^2}\frac{t-1}{\sqrt t}dt\Rightarrow I'(a)=\int_0^\infty \frac{(t-1)\sqrt t}{(1+a^2 t^2)(1+t^2)}dt$$ $$\overset{t=x^2}=\frac{2}{1-a^2}\int_0^\infty \frac{1+a^2 x^2}{1+a^2 x^4}dx-\frac{2}{1-a^2}\int_0^\infty \frac{1+x^2}{1+x^4}dx=\frac{\pi}{\sqrt 2}\frac{1-\sqrt a}{\sqrt a (1+a)(1+\sqrt a)}$$


$$\Rightarrow I=\frac{\pi}{4}\int_0^1 \frac{1-\sqrt a}{\sqrt a (1+a)(1+\sqrt a)}da\overset{\sqrt a=x}=\frac{\pi}{2}\int_0^1 \frac{1-x}{(1+x^2)(1+x)}dx=\frac{\pi}{4}\ln 2 $$

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ Thanks a lot!!! $\endgroup$ – Grentouce Jul 25 '19 at 12:07
  • 1
    $\begingroup$ Yeah its clear! $\endgroup$ – Grentouce Jul 25 '19 at 12:08
  • 1
    $\begingroup$ @TheCoolDrop if we consider $f(x)=\ln(\sin x+\cos x+\sqrt{\sin(2x)})$ then notice that: $$\int_0^\frac{\pi}{2} f(x)dx=\int_0^\frac{\pi}{4} f(x) dx +\int_\frac{\pi}{4}^\frac{\pi}{2} f(x) dx$$ Now let $\frac{\pi}{2}-x =t$ and notice that $f(\pi/2-t)=f(t)$ to get: $$\int_\frac{\pi}{4}^\frac{\pi}{2} f(x) dx =\int_0^\frac{\pi}{4} f(t) dt\Rightarrow \int_0^\frac{\pi}{2} f(x)dx=2\int_0^\frac{\pi}{4} f(x) dx $$ $\endgroup$ – Zacky Jul 25 '19 at 12:50
  • 1
    $\begingroup$ Very elegant solution, for sure. $\endgroup$ – Claude Leibovici Jul 25 '19 at 12:59
  • 2
    $\begingroup$ With the substitution $\frac{\pi}{2}-x=t\Rightarrow dx=-dt$ we get: $$\int_\frac{\pi}{4}^\frac{\pi}{2}f(x)dx=\int_\frac{\pi}{4}^0 f\left(\frac{\pi}{2}-t\right)(-dt)=\int_0^\frac{\pi}{4} f\left(\frac{\pi}{2}-t\right)dt$$ $\endgroup$ – Zacky Jul 25 '19 at 14:09
4
$\begingroup$

Here is a different solution using complex method. We can notice that

\begin{align*} I = &\int_0^{\frac \pi 4} \ln\left(1+\tan x + \sqrt{2\tan x} \right) dx + \int_0^{\frac\pi 4} \ln(\cos x) dx \\ = &I_1 + I_2. \end{align*} Evaluation of $I_1$ : Let $\displaystyle\omega = e^{\frac {\pi i} 4} =\frac{1+i}{\sqrt 2}$ and make substitution $\tan x= y^2 $ to find that \begin{align*} I_1 =& \int_0^1 \log\left((1+\omega y)(1+\bar \omega y)\right)\frac{2y }{1+y^4}dy \\ =& 4 \Re \int_0^1 \frac{y \log\left(\frac{1+\omega y}2 \right)}{1+y^4} dy +\frac {\pi\ln 2}2. \end{align*} Let $\omega y = z$. Then using $\omega^2 = i, \omega^4 = -1$, \begin{align*} \Re \int_0^1 \frac{y \log\left(\frac{1+\omega y}2 \right)}{1+y^4} dy =& \Re \int_0^\omega \frac{ \frac{z}{\omega} \log\left(\frac{1+z}{2}\right)}{1+ (\frac z \omega)^4} \frac{dz}\omega \\ =& \Im \int_0^\omega \frac{z \log\left(\frac{1+z}{2}\right)}{1-z^4} dz \\ =& \frac 1 2 \Im \int_{-\omega}^\omega \frac{z \log\left(\frac{1+z}{2}\right)}{1-z^4} dz. \end{align*} Note that $\displaystyle f(z) = \frac{z \log\left(\frac{1+z}{2}\right)}{1-z^4} $ is analytic in $|z|<1$, and continuous in $|z|\le 1$ except at points $\displaystyle -1, \pm i$. So by choosing a contour $z = e^{i\theta}, -\frac \pi 4\le \theta \le \frac \pi 4$ and using $\log(1+e^{i\theta}) = \log\left(2\cos\left(\frac \theta 2\right)\right) + \frac {i\theta}{2}$, etc, we get \begin{align*} \Im \int_{-\omega}^\omega \frac{z \log\left(\frac{1+z}{2}\right)}{1-z^4} dz =&\Im \int_{-\frac \pi 4}^{\frac \pi 4} \frac{ie^{i2\theta}\left(\log(\cos (\theta/2)) + i\theta/2\right)}{1-e^{i4\theta}} d\theta\\ =&-\Im \int_{-\frac \pi 4}^{\frac \pi 4} \frac{\log(\cos (\theta/2)) + i\theta/2}{2\sin(2\theta)} d\theta\\ =& -\frac 1 4\int_{-\frac \pi 4}^{\frac \pi 4} \frac{\theta}{\sin(2\theta)} d\theta\\ =& -\frac 1 4 \int_{0}^{\frac \pi 4} \frac{\theta}{\sin\theta \cos \theta} d\theta\\ =:& -\frac 1 4 J \end{align*} (In fact $J = G$, the Catalan's number.) This gives $$ I_1 = -\frac 1 2 J +\frac {\pi \ln 2}2. $$

Evaluation of $I_2$ : By integrating by parts, we have \begin{align*} I_2 =& x\ln(\cos x)|^{\frac \pi 4}_0 +\int_0^{\frac \pi 4} \frac {x \sin x}{\cos x} dx \\ =&-\frac{\pi \ln 2}{8} +K. \end{align*} We observe that \begin{align*} K-J = & -\int_0^{\frac \pi 4} \frac{x\cos x}{\sin x} dx\\ =& -x\log(\sin x)|^{\frac \pi 4}_0 + \int_0^{\frac \pi 4} \log(\sin x) dx\\ =& \frac{\pi \ln 2}{8} + \int_{\frac \pi 4}^{\frac\pi 2} \log(\cos x) dx \tag{$\frac \pi 2 - x\mapsto x$}\\ =&-\frac{3\pi \ln 2}{8} -I_2 \end{align*} thus $\displaystyle K = -\frac{3\pi \ln 2}{8} -I_2 +J$ and $$ I_2 = -\frac{\pi \ln 2}{2} -I_2 +J \Longrightarrow I_2 = \frac 1 2 J -\frac{\pi \ln 2}{4}. $$ Therefore, we have $$ I = I_1 + I_2 = \left(-\frac 1 2 J +\frac{\pi\ln 2}2\right)+\left(\frac 1 2 J -\frac{\pi \ln 2}{4}\right) = \frac {\pi \ln 2}4. $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Wow! Amazing one! Thanks a lot! $\endgroup$ – Grentouce Jul 27 '19 at 7:30
  • $\begingroup$ I hope it was helpful! :) $\endgroup$ – Song Jul 29 '19 at 3:50
  • $\begingroup$ It was helpful :) $\endgroup$ – Grentouce Jul 29 '19 at 4:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.